Reliability modeling framework of satellite constellation based on three-parameter interval grey number Lz transformation - Ruirui Shao; Weiqing You; Yuanyuan Nie (Scientific Reports)
Abstract The performance of in-orbit communication satellites generally degrades over time due to depletion mechanisms, rendering them multistate systems with varying output performance levels. This paper applies grey system theory to the reliability assessment of multistate systems, specifically addressing the performance degradation and data scarcity characteristics inherent in communication satellites. A grey multi-state system model is developed to capture these dynamics. Considering the satellite’s structural characteristics, the reliability solution algorithm incorporates the potential for performance levels exceeding required thresholds. This integration is achieved by combining the grey universal generation function with the grey Markov process, using the three-parameter interval grey number as an intermediary function. Through the Lz transformation based on three-parameter interval grey numbers, the proposed dynamic reliability assessment model for multi-state communication satellites effectively mitigates challenges associated with high-dimensional state spaces in satellite systems. The developed model provides robust methodological support for reliability assessment of complex grey multistate systems.